Análise de variáveis que influenciam na taxa de sucesso da indução do parto com Misoprostol no Hospital das Clínicas da Universidade Federal de Minas Gerais (UFMG) - Thayane Delazari Corrêa (2021)
Introduction: Induction of labor refers to techniques for stimulating uterine contractions leading to labor. Misoprostol has been used to induce labor since the 1990s, but its use is still off label. As induction with oxytocin is less effective in patients with low scores on the Bishop index, the cervical ripening process with misoprostol is indicated in those women. Objective: Determine the predictive criteria for success in cervical ripening in inducing labor for live fetuses using misoprostol in pregnant women admitted in Maternidade Otto Cirne at the Hospital das Clínicas, UFMG. Methodology: The medical records of 873 pregnant women admitted for cervical maturation from January 2017 to December 2018 were reviewed, with analysis of the following response variables: age, parity, uterine height, Bishop Index, number of tablets and doses of misoprostol, number of vaginal touches, use of oxytocin, labor induction time, amniotomy/ amniorrhexis and amniotic fluid aspect. Logistic regression models and classification trees were used to predict success with misoprostol in non-operative and uncomplicated deliveries. Results: Of the 873 patients evaluated, 72% evolved with vaginal delivery, 23% of the cases were cesarean, 5% forceps or vacuum-extractor. For non-operative delivery and delivery without complications, the predictive variables at admission were age, parity, gestational age and dilation. During hospitalization, the less vaginal touches, amniotomy/ amniorrhexis with clear liquid, the shorter the induction time and the number of vaginal touches, the greater the chance of non-operative delivery. False positives and false negatives were always below 50% and the percentage of correct answers above 65%. Conclusion: At admission, the younger the child (less than 24 years), the more previous normal births, the lower the gestational age and the greater the dilation, the greater the probability of non-operative delivery. During hospitalization, the smaller number of vaginal touches, amniotomy/amniorrhexis with clear fluid and shorter labor induction time were associated with a greater chance of non-operative delivery. Future studies with a prospective design and analysis of other factors are necessary to assess the replicability, generalization of these findings and improvement of the forecast.